A Simple, Rapid, and Highly Sensitive Magnetic Beads ELISA for Detection of SARS CoV-2 Antibodies (IgG) in Human Plasma Samples as a Point of Care Assay - Bhatia, S.; Бхатія, С. (PH "Akademperiodyka" of the NAS of Ukraine, 2023)
The pandemic outbreak of coronavirus (SARS CoV-2) has been going on over the last 3 years. The people are vaccinated with different vaccines targeting the S protein. Aim. Therefore, it is essential to have an assay that can detect different parts of the virus as a serological assay and can be performed as a point of care test. Hence, in this work, we decided to develop such an assay with the help of magnetic beads. Methods. The magnetic beads ELISA (MB ELISA) was developed in a microtube. The viral ligand-specific magnetic beads were used to detect the nucleoprotein (NP)-specific IgG antibodies in human plasma samples. The results were read with the naked eye as well as with professional ELISA readers. Results. 7 μL magnetic beads were suitable to detect the presence of NP-specific antibodies. The assay needs only a magnetic rack and a pipettor to be performed. The results were available within 30 min. The positive results were observed as yellow color visually but also read in ELISA reader as OD values. The sensitivity of this assay was 1:108 dilutions. The cross-reaction panel was negative with different pathogens and negative human plasma. Conclusions. This work may be the first report in literature about the development of a magnetic beads ELISA as a point of the care assay, which is reproducible, highly sensitive, robust, and easy to perform. It was used to detect the presence of NP-specific IgG antibodies in the plasma samples successfully. This assay can be used as a professional assay, where the results can be measured with an ELISA reader. This assay may be suitable in small clinics also under field conditions. It can be used to detect the SARS CoV-2 infection in vaccinated persons (S protein-based vaccines) along with non-vaccinated population in latent and active phase.